Finite size effects in the thermodynamics of the free scalar field and the interacting SU(3) plasma - Mohamed, Husam (Department of Physics, 2019)
In this thesis, we study the thermodynamic properties of the free scalar field and the thermodynamics of the interacting SU(3) plasma when these systems are away from the thermodynamic limit, i.e., at finite volume. In the first part of the thesis, we study the thermodynamic properties of the free scalar field in a variety of finite-size geometries (the cube, the cuboid and the parallel-plates geometries) when the field is subjected to Dirichlet and periodic boundary conditions; we also give a brief review of the thermodynamic properties of the free scalar field on discretized Euclidian space-time lattices. In the second part of the thesis, we discuss briefly the thermodynamic properties of the quark-gluon plasma in the continuum and thermodynamic limits, and then we use a quasi-particle model of the SU(3) plasma to shed some light on the interplay of finite-size and generic interaction effects in the context of lattice QCD calculations.